Studies of Chilean fungi i: metabolites in ramenia flaccida (fr.) Ricken var. Chilensis tie - Torpoco Carmen, Virginia (2012)
From fruit bodies of Ramaria flaccida (Fr.) Ricken var. chilensis Lazo, were isolated ergosterol, peroxiergosterol, as well as myristic, palmitic, stearic, oleic, linoleic and linoleic acids. Structures of these metabolites were deduced by means of spectroscopic analysis mass, RMN 1H and RMN 13C.